Up-skilling the next generation of researchers to analyse complex linked population-level datasets: ADR UK PhD studentships case study - Mir, Saba; Oliver, Emily; Gordon, Emma (International Journal of Population Data Science, 2024)
Objective Administrative Data Research UK (ADR UK) has invested £1.9M in its first pilot PhD scheme, as part of a larger Training and Capacity Building Strategy to increase the capability of researchers trained to analyse complex linked population-level datasets. This session will highlight the successes and lessons learned in the first year of implementing this pilot in the context of a wider strategic drive to increase the number of data skills-focused PhD students in the UK. Approach 22 PhD projects from across the UK were selected for funding by an independent panel of experts. Students and supervisors joined a unique cohort receiving targeted support from ADR UK. Activities, events and resources were devised with advice from existing users of the data, including regular events and check-ins, training opportunities, an online Learning Hub and noticeboard, and establishment of themed networks and communities. Results Supporting cross-disciplinary cohorts of students and supervisors who span the UK has come with its own challenges. These include accessing data through different models and gateways, addressing a variety of skills gaps, and developing community building approaches that address multiple needs and which sustain the momentum beyond formal in-person events. Conclusions & Implications ADR UK's targeted support model will continue to evolve to ensure the students in this PhD cohort make the most of their experiences. We welcome the opportunity to connect with international colleagues about their experiences of programmes designed to up-skill the next generation of researchers to analyse complex linked population-level datasets.